Evaluation of time to antibiotic therapy after implementation of an updated rapid diagnostic test for gram-negative bacteremia - Rawan Hussein; Leslie Lee; Rajat Nog; Donald Chen; Vishnu Chaturvedi; Nicholas Feola (Journal of Clinical Microbiology, 2026)
ABSTRACT Rapid pathogen identification optimizes antibiotic therapy in bacteremia and can be achieved through molecular-based diagnostic tests. This study assesses the clinical impact after the implementation of an updated multiplex PCR panel (BIOFIRE Blood Culture Identification 2, BCID2). This single-center, retrospective, quasi-experimental study compared outcomes in adult patients with gram-negative bloodstream infections (GN-BSIs) pre and post BCID2 implementation. Data were collected from 1 March 2022 to 1 March 2024. Patients were included if they were ≥18 years of age, had a gram-negative organism identified by the panels, and received ≥48 h of antibiotics. The primary outcome was time to effective antimicrobial therapy; secondary outcomes included time to appropriate therapy, 30-day mortality, and hospital length of stay. A total of 180 patients were included (90 per BCID and BCID2 groups). Baseline characteristics were similar: median age 62 years, mostly non-critically ill, Charlson Comorbidity Index 4, and Pitt Bacteremia score 1 in both groups. Median time to effective therapy was reduced in the BCID2 vs BCID group (1 vs 4 h, P = 0.004) as well as time to appropriate therapy (25 vs 49 h, P = 0.627). In the ESBL subgroup, BCID2 significantly reduced time to effective therapy (0.5 vs 3 h, P = 0.006) and time to appropriate therapy (16 vs 44 h, P = 0.016). There was no significant difference in mortality (6.7% vs 8.9%, P = 0.756) or length of stay (10 vs 14 days, P = 0.134) between BCID and BCID2 groups. The implementation of BCID2 significantly reduced time to effective therapy in GN-BSIs, particularly among resistant organisms. IMPORTANCE This study evaluated the impact of transitioning from BCID to BCID2 panel in gram-negative bloodstream infections to address gaps in resistance detection and assess whether expanded molecular diagnostics improve time to antibiotic therapy and clinical outcomes.